Ifá Guiding Principles in Pre-Marital Counselling Towards a Happy Family - Akinola Segun Gabriel (Africajournals, 2022)
The high rate of divorce among both young and older couples is on an increase with several unhappy families living in frustration and uncertainty. This is tied to their unpreparedness before going into marriage and their incompatibility as destiny may not permit the union of both couples in the first place. Though, physical or psychological counselling are important these have not proved effective enough to solve marital problems. The spiritual dimension of views, the unseen, as a way of guidance before going into marriage has becomes imperative in solving marital situations that have atrophied the family settings and the society at large. It is on this basis, that the essence of Ifa divination in enquiring into the fate of a couple coming together as one in holy matrimony cannot be undervalued. In other words, it is a structural foundation towards building a happy marriage. The Christian Orthodox worldview on counselling is also touched upon as a means of comparison with the oldest Christian denomination. The spiritual compatibility of the couple is important, and far more than the physical understanding of blood group genotype, temperament, sexual compatibility, communication skill etc. This paper, therefore, aims at establishing the place of Ifa divination in a couple’s pre-marital counselling, as an important requirement before going into marriage. Twenty (20) Ifa priests were interviewed across southwestern Nigeria. Collections of information were content analysed, resulting in a recommendation for spiritual enquiries into the compatibility of couples before going into marriage